2017
DOI: 10.1124/mol.117.110379
|View full text |Cite
|
Sign up to set email alerts
|

RVX-297, a BET Bromodomain Inhibitor, Has Therapeutic Effects in Preclinical Models of Acute Inflammation and Autoimmune Disease

Abstract: Bromodomain (BD) and extra-terminal domain containing proteins (BET) are chromatin adapters that bind acetylated histone marks via two tandem BDs, BD1 and BD2, to regulate gene transcription. BET proteins are involved in transcriptional reprogramming in response to inflammatory stimuli. BET BD inhibitors (BETis) that are nonselective for BD1 or BD2 have recognized anti-inflammatory properties in vitro and counter pathology in models of inflammation or autoimmune disease. Although both BD1 and BD2 bind acetylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 56 publications
1
60
0
Order By: Relevance
“…Recent studies focused on the oral administration of BET inhibitors 36 37 85 or the use of BRD2-selective inhibitors such as RVX-297. 37 The good druggability of BRD will likely lead to the continuing development of inhibitors that will further boost the research in this field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies focused on the oral administration of BET inhibitors 36 37 85 or the use of BRD2-selective inhibitors such as RVX-297. 37 The good druggability of BRD will likely lead to the continuing development of inhibitors that will further boost the research in this field.…”
Section: Discussionmentioning
confidence: 99%
“… 60 67 Recently, the use of a BDR2 specific and orally active BET inhibitor, RVX-297, was shown to be efficient in decreasing the arthritis scores in CIA mice and rats, as well as in mice with collagen antibody-induced arthritis. 37 The beneficial effects of BET inhibitors in arthritis models in vivo were mainly attributed to the suppressive effects on Th17 cell differentiation and the reduced expression of Th17-associated cytokines, including IL17, IL21 and granulocyte macrophage-colony stimulating factor. 34 37 The aberrant generation and activation of Th17 cells, a subset of T helper cells, is one of the key mechanisms leading to autoimmune conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Brd2 and Brd4 physically associate with the promoters of inflammatory cytokine genes, reducing production of cytokines TNFα, IL-6, MCP-1 in vitro and in vivo. Also, one study on the transgenic model of AD (3×Tg mice) confirmed the important function of BET proteins in regulating brain gene expression in neuro-inflammation-related conditions, including AD [80]. Importantly, Brd3 gene is Ca 2+ -responsive gene [81].…”
Section: Discussionmentioning
confidence: 90%
“…A growing body of evidence indicates that epigenetic control mechanisms are involved in regulating the immune system. Recent studies confirmed that BET proteins may affect the progression of inflammation and demonstrated that they are critical for macrophage activation [35,[77][78][79][80]. Brd2 and Brd4 physically associate with the promoters of inflammatory cytokine genes, reducing production of cytokines TNFα, IL-6, MCP-1 in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 91%
“…It is interesting that BET proteins are critical for inflammatory response and Brd2 is essential for pro-inflammatory cytokine production [59]. Emerging preclinical and clinical evidence show a number of small molecule BET inhibitors with a potent anti-inflammatory activity [60,61]. Thus, the reduced inflammation observed in HET kidneys could be due to Brd2's up-regulation of cytoprotective genes when it is haplodeficient, but it could also be due to a down-regulation of pro-inflammatory genes.…”
Section: Longevity Genes and Kidney Pathologymentioning
confidence: 99%